2014
DOI: 10.1007/s00402-014-1996-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the anteromedial and transtibial drilling technique in ACL reconstruction after a short-term follow-up

Abstract: It was shown that AMP technique was superior to the TT technique in providing anatomical placement of the graft and in recovery time to return sports; however, there was no difference between groups in early periods in terms of the clinical and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Although evaluation of the functional outcomes based on IKDC and Lysholm scores and Tegner activity levels revealed higher values in the AMP group, significant differences between the groups were not observed. This result is similar to the results of other studies with more than a year of follow-up time [ 11 , 29 , 32 , 33 ]. Conversely, there are studies with significantly higher IKDC and/or Lysholm scores following ACL reconstruction using the AMP technique [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although evaluation of the functional outcomes based on IKDC and Lysholm scores and Tegner activity levels revealed higher values in the AMP group, significant differences between the groups were not observed. This result is similar to the results of other studies with more than a year of follow-up time [ 11 , 29 , 32 , 33 ]. Conversely, there are studies with significantly higher IKDC and/or Lysholm scores following ACL reconstruction using the AMP technique [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, numerous studies have suggested that the AMP technique facilitates a more anatomic and horizontal femoral tunnel, independent of tibial tunnel placement within the native ACL femoral attachment site, and provides greater rotational stability. Furthermore, these studies suggest that a more horizontal placement of the graft decreases the risk of graft impingement [ 10 , 29 , 30 ]. However, there are several potential surgical difficulties with regard to the AMP technique, including a short femoral tunnel, blow out of the back wall of the lateral femoral intercondylar notch, and difficulty with visualization and graft passage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like several techniques of femoral tunneling, AMP drilling may provide improved rotation stability, decreased anterior translation and greater coverage of ACL’s anatomic footprint compared to TT techniques, but there is little evidence to support a clinical difference[6,9-12]. To this end, clinical outcomes of TT and AMP drilling techniques for ACL reconstruction were directly appraised in a 2016 systematic literature review, however all outcomes suggesting superior result of AMP drilling technique failed to surpass a minimal clinically important difference despite notable improvements based on the physical exam and scoring system results[6].…”
Section: Resultsmentioning
confidence: 99%
“…Few other studies did not find any significant difference between both the techniques on the basis of IKDC, Lysholm and Tegner scale scores. [22][23][24] Smaller sample size, less adequate measurement of the degree of post-operative stability and less duration of follow-up remains the limitations of the study.…”
Section: Discussionmentioning
confidence: 99%